Uncertainty modeling in dose response : bench testing environmental toxicity - Cooke, Roger M., 1946- (Statistics in practice., 2009)
A valuable guide to understanding the problem of quantifying uncertainty in dose response relations for toxic substances. In today's scientific research, there exists the need to address the topic of uncertainty as it pertains to dose response modeling. Uncertainty Modeling in Dose Response is the first book of its kind to implement and compare different methods for quantifying the uncertainty in the probability of response, as a function of dose. This volume gathers leading researchers in the field to properly address the issue while communicating concepts from diverse viewpoints and incorpor.